2018
DOI: 10.1111/head.13387
|View full text |Cite
|
Sign up to set email alerts
|

American Headache Society Survey About Urgent and Emergency Management of Headache Patients

Abstract: A substantial number of headache specialists are dissatisfied with the care their patients receive in the ED. More standardized protocols for ED visits by patients with known headache disorders, and clear guidelines for communication between ED providers and treating physicians, along with better methods for follow-up following discharge from the ED, might appear to improve this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The treatment provided was adequate for the majority of consultations. There was excessive use of opioids, contrary to the recommendations of the Brazilian Headache Society and the International Headache Society 2,8 . However, similar conduct, and with even higher rates of opioid use, is also found in the American population, where a substantial proportion of headache specialists are dissatisfied with the treatment offered by emergency services 8 .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The treatment provided was adequate for the majority of consultations. There was excessive use of opioids, contrary to the recommendations of the Brazilian Headache Society and the International Headache Society 2,8 . However, similar conduct, and with even higher rates of opioid use, is also found in the American population, where a substantial proportion of headache specialists are dissatisfied with the treatment offered by emergency services 8 .…”
Section: Discussionmentioning
confidence: 65%
“…The medication most commonly administered was dipyrone, followed by antiemetics and corticosteroids. Despite the recommendations of the Brazilian Headache Society and the International Headache Society 2,8 , which advise against use of opioids for migraine, these drugs were used for 30.2% of the individuals diagnosed. Moreover, those who received opioids were twice as likely to experience migraine.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, to improve the standardization of migraine care, perhaps urgent care providers could use the MAP or a modified version . Prior research has already shown the need for better communication and consistency between headache specialists/neurologists and acute care physicians for the optimization of acute migraine treatment . We suggest that a system can be developed to ensure adequate follow‐up of urgent care visits.…”
Section: Discussionmentioning
confidence: 99%
“…21 Prior research has already shown the need for better communication and consistency between headache specialists/neurologists and acute care physicians for the optimization of acute migraine treatment. 22 We suggest that a system can be developed to ensure adequate follow-up of urgent care visits.…”
Section: Discussionmentioning
confidence: 99%
“…The most common headache disorders are migraine, tension-type headache (TTH) and trigeminal autonomic cephalalgias (TACs). Moreover, in many recent studies, headache is reported as one of the most frequent admitting symptoms to the emergency department, even if it has been well stated that the ED is a suboptimal place for headache treatment, suggesting that an urgent admission to a headache centre should be preferred even in the acute headache attacks [1].…”
mentioning
confidence: 99%